The Demise of Investment Banking Partnerships: Theory and Evidence - MORRISON, ALAN D.; WILHELM, WILLIAM J. (Journal of Finance, 2008)
ABSTRACT In 1970 the New York Stock Exchange relaxed rules that prohibited the public incorporation of member firms. Investment banking concerns went public in waves, with Goldman Sachs the last of the bulge bracket banks to float. We explain the pattern of investment bank flotations. We argue that partnerships foster the formation of human capital and we use technological advances that undermine the role of human capital to explain the partnership's going‐public decision. We support our theory using a new data set of investment bank partnership statistics.